Caffeine improves the developmental competence of parthenogenetic embryos derived from aging porcine oocytes - Thuy Van, Nguyen Thi; Truong Duy, Pham; Thuan, Nguyen Van; Thuy, Bui Hong (Vietnam Journal of Biotechnology, 2020)
Oocytes are committed to deterioration in quality as they aged due to a long duration manipulation which leads to the reduced success rate of somatic cell nuclear transfer (SCNT). Caffeine with an effect to maintain the maturation-promoting factor (MPF) from the metaphase of oocytes is expected to enhance the quality of the aging oocytes. To investigate the timely treatment of caffeine to rescue aging oocytes, caffeine was supplemented after in vitro maturation (IVM) or during metaphase I – metaphase II (MI – MII) transition. First, the effect of caffeine after IVM of oocytes was examined. After IVM for 42 h, oocytes were left for aging within 6 or 8 hours in supplement with various concentrations of caffeine (0, 5 and 10 mM), and  then, examined the quality of embryo from aged oocyte through parthenogenesis activation. We found that 5 mM caffeine for the first 6 hours of aging process was suggested to improve the early development of parthenogenetic diploid embryos. However, the cytoplasmic homogeneity is significantly reduced in aging oocyte compared to fresh oocyte and it could not be improved by caffeine treatment. Next, the effect of caffeine during MI – MII transition of oocyte was examined. Caffeine was supplemented during MI – MII transition (27 – 42 h) of IVM. Then mature oocytes were left for aging within 6 h to examine on aging porcine oocyte quality via parthenogenesis embryos. The results indicated that 5 mM caffeine during MI-MII transition could efficiently rescue aged oocytes and improve the development of embryos derived from aging oocytes to four-cell, eight-cell and blastocyst stage as compared to fresh oocytes. Especially, these aged oocytes treated by caffeine could improve the cytoplasmic homogeneity in embryos and the quality of blastocysts by increasing cell number similar to fresh oocytes.